2017
DOI: 10.1007/s13744-017-0525-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resource Density on Energy Allocation in the Neotropical Termite Nasutitermes aff. coxipoensis (Termitidae: Nasutitermitinae)

Abstract: Organisms acquire energy from environment and must allocate it among different life traits (growth, maintenance and reproduction). Social insects must manage the energy allocation to various levels such as colony growth and caste functions. Here, we addressed the question of whether resource density affects the energy allocation to the number of individuals and caste functions as well as nest's growth rate in the Neotropical termite Nasutitermes aff. coxipoensis (Homgren) (Termitidae: Nasutitermitinae). In a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Foraging is a crucial behavior which have signi cant impact on their life history characteristics (Bloom 2012). The rate of energy input to any animal will basically depend on the resources selected during foraging (Boggs 1992; Boggs 2009), which consequently affect the energy allocated to survival (growth, maintenance, defense) and reproduction (Stearns 1989;Cristaldo et al 2018). Therefore, it is expected that animals optimize their tness selecting food resources during foraging that will provide high energy input with low costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foraging is a crucial behavior which have signi cant impact on their life history characteristics (Bloom 2012). The rate of energy input to any animal will basically depend on the resources selected during foraging (Boggs 1992; Boggs 2009), which consequently affect the energy allocated to survival (growth, maintenance, defense) and reproduction (Stearns 1989;Cristaldo et al 2018). Therefore, it is expected that animals optimize their tness selecting food resources during foraging that will provide high energy input with low costs.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this must be related to energy allocation to colony growth (number of individuals) and caste function. Empirical studies have been shown that number of individuals in the colony and the production of castes in both lower and higher termites' species are affected by resource quantity(Lenz 1994;Korb 2004; Korb and Katrantzis 2004;Korb and Schmidinger 2004;Cristaldo et al 2018). Same pattern was already observed in ants(Aron et al 2009;Wills et al 2015) and bees(Carvell et al 2008;Smith et al 2012…”
mentioning
confidence: 99%
“…According to Grüter and Leadbeater (2014), species able to combine exploitation of food resources with exploration of new food sources should benefit over species that use only one of these strategies. Although the mechanisms that determine foraging decisions in termites are still poorly studied, there is evidence that resource availability plays a key role in foraging modulation (see Araújo et al., 2007, 2017; Cristaldo, Almeida, et al, 2018; Cristaldo, Araújo, et al, 2016; Ferreira, Cristaldo, et al, 2018; Ferreira, Sacramento, et al, 2018). In addition, some studies have shown that the role of social information depends on many factors, including the quantity and distribution of the resource, the changes rate of the environment, the strategies of competitors, and also the predators’ pressure (Lee et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the amount of wood available regulates how severely Coptotermes formosanus Shiraki (Rhinotermitidae) build foraging tunnels (HEDLUND; HENDERSON, 1999). Similarly, Cristaldo et al (2018) have observed that the number of worker of Nasutitermes aff. coxipoensis (Holmgren) (Termitidae) has linearly increased due to increased food-source density (0.32, 0.64 and 1.92 baits/m 2 ).…”
Section: Introductionmentioning
confidence: 99%